Facile single-step technique for simultaneous in situ fabrication of Ag/Ag2S-polymer nanocomposites via PPS cyclization route - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Seth, Tanay; Amalnerkar, Dinesh P. (Chemistry Letters, 2008)
We herein propose a facile single-step approach involving solid-state reaction between silver salt and engineering thermoplastic polyphenylene sulfide for simultaneous in situ generation of nanoscale metallic silver as well as semiconducting silver sulfide.

Kinetics of PbCrO(4) nanorod growth by oriented attachment at the air-water interface - Hawaldar, Ranjit R.; Sathaye, Shivaram D.; Harle, Arti S.; Gholap, Ramkrishna S.; Patil, Kashinath R. (Journal of Physical Chemistry C, 2008)
Oriented attachment is a new way of crystal growth to transform preformed nanoparticles into hierarchical assemblies. Here, we demonstrate the use of liquid-liquid interfaces toward the formation of PbCrO(4) nanoparticles and their subsequent time-dependent self-assembly at the air-water interface into nanorods by oriented attachment. EDAX and XPS analysis indicate the formation of stoichiometric PbCrO(4). TEM studies at different stages of aging reveal that the transformation from nanoparticles to nanorods is kinetically governed. HRTEM analysis indicates nanorod growth along the [110] plane. UV-visible spectra reveal the presence of peaks at 425 and 515 nm for nanorods, while for the nanoparticle sample, a single peak at 425 urn is evident. As formation of ultrathin films over a large area (typically equal to or greater than 1 mu m x 1 mu m) concomitantly accompanies this approach, it can be extended to other materials as well for nanostructured device applications.

Synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Materials Chemistry and Physics, 2008)
In the present investigation the synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial has been reported. The material was synthesized by coprecipitation process combined with surfactant incorporating method. The concentration level of Ce (III) additive was varied systematically from 1 to 11 wt.%. After calcinations at500 degrees C,a high BET surface area of 40 m(2)/g was obtained for 7 wt.% CeO2. The effect of variation of sintering temperature (600-800 degrees C/2h) on the particle size and surface area of a CeO2/SnO2 system was investigated. The material obtained was nanocrystalline, having particle size in the range of 10-16 nm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CeO2:SnO2; Nanomaterials; sensors

Synthesis and characterizations of NiTiO(3) nanoparticles prepared by the sol-gel process - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Mandale, A. B.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2008)
Nanocrystalline nickel titanate (NiTiO(3)) composite powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 750 degrees C for 2 h in air. The results revealed that a pure hexagonal phase of NiTiO(3) could be obtained at the low temperature of 750 degrees C. The phase evolution of NiTiO(3) was investigated by X-ray diffraction patterns, Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy. Particle size and morphology were studied by transmission electron microscopy.
Keywords: Nanoparticles; nickel titanate; sol-gel process

Concurrent In-situ formation of Ag/Ag2S nanoparticles in polymer matrix by facile polymer-inorganic solid state reaction - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Hawaldar, Ranjit R.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Journal of Nano Research, 2009)
We herein report the feasibility of polymer-inorganic solid-state reaction route for simultaneous in situ generation of Ag & Ag2S nanostructures in polymer network wherein an engineering thermoplastic, polyphenylene sulphide (PPS), itself acts as a chalcogen source as well as a stabilizing matrix for the resultant nanoproducts. Typical solid-state reaction was accomplished by simply heating the physical admixture of the two reactants i.e. AgNO3 and PPS by varying molar ratios mainly 1:1, 1:5, 1:15, 1:20, at the crystalline melting temperature (285 degrees C) of PPS. The synthesized nanoparticles were characterized by various physico-chemical techniques like X-ray Diffractometry, Scanning Electron Microscopy equipped with EDAX, Transmission Electron Microscopy and UV-Visible spectroscopy. The prima facie observations suggest the effective formation and subsequent entrapment of mainly nanocrystalline metallic silver (fcc) in PPS matrix for all the molar ratios chosen for the reaction. Additionally, simultaneous occurrence of nanocrystalline Ag2S (monoclinic phase) is also noticed in case of heated admixture of AgNO3: PPS with equimolar ratio. The TEM analysis reveals nanoscale polydispersity (5nm to 70nm) and prevalence of mainly spherical morphological features in all the cases with occasional indications of triangular and hexagonal morphological features depending upon the reaction molar ratio.
Keywords: Ag; Ag2S; Nanoparticles; Polymer inorganic solid -state reaction; Thermoplastic polymer matrix

Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Interfacial and physico-chemical properties of polymer-supported CdS center dot ZnS nanocomposites and their role in the visible-light mediated photocatalytic splitting of water - Deshpande, Aparna; Shah, Pallavi; Gholap, Ramkrishna S.; Gupta, Narendra M. (Journal of Colloid and Interface Science, 2009)
Nano-composite CdS center dot ZnS moieties coated over polyester strip were found to exhibit better visible-light-mediated photo-activity for splitting of water, as compared to corresponding pure CdS or ZnS containing coupons. This increase in activity depended upon the mol ratio of the two component sulphides in a particular sample. HRTEM experiments revealed the presence of 1-3 nm size CdS particles embedded over larger size ZnS clusters, the composite samples thus functioning as a highly dispersed guest-host system. In the case of CdS and ZnS dispersed individually over polyester, average crystallite size was found to be around 5 and 15 rim, respectively. A blue shift was observed in the UV-vis absorption spectrum of US oil addition of ZnS, in conformation with the quantum size effects. Powder XRD, electron diffraction and XPS Studies showed that the nanocomposites were comprised of the face-centered cubic (alpha) phases of both US and ZnS in a close contact with each other. At the same time, certain solid solution phases, i.e. Cd(1-x)Zn(x)S. were generated at the interfaces of these two semiconductors. Our Study demonstrates that the increase in the number of reaction sites due to smaller size of US particles and the micro-structural properties associated with the nanostructured US or CdS/ZnS interfaces may together play a vital role in the augmented catalytic activity of CdS center dot ZnS composite photocatalysts. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: CdS center dot ZnS nanocomposites; Photocatalytic activity; Role of microstructural properties; Splitting of water

Physico-chemical, photo-catalytic and O-2-adsorption properties of TiO2 nanotubes coated with gold nanoparticles - Malwadkar, Sachin S.; Gholap, Ramkrishna S.; Awate, Shobhana V.; Korake, Prakash V.; Chaskar, Manohar G.; Gupta, Narendra M. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Gold-containing titania nanotubes (Au/NT) were found to display higher activity for photooxidation of acetaldehyde, as compared to corresponding gold-free nanotubes and also a Degussa P-25 catalyst. Besides CO2 as a major reaction product, small amounts of H-2, CH4, CO, H2O and CH3COOH were also formed, irrespective of the catalyst employed. High-resolution TEM examination showed that most of the gold particles in Au/NT were of 1.5-5 nm size, distributed both within and at outside surface of the nanotubes. Some larger size (10-70 run) clusters were also seen at the external surfaces, particularly in the samples calcined at an elevated temperature. The temperature-programmed desorption measurements revealed that, compared to P-25 TiO2, a significant entrapment of O-2 occurred at two distinct tubular sites of NT samples, corresponding activation energy of desorption (E,) being around 36 and 41 kcal mol(-1). On the other hand, gold nanoparticles in Au/NT served as independent low-energy (E-a = 26 kcal mol(-1)) sites for adsorption/activation of O-2. These adsorptive properties of TiO2 and Au were lost completely on calcination, thus revealing a crucial role played by the particle size. In situ IR spectroscopy results showed that room-temperature exposure to acetaldehyde + air gave rise to a molecularly bound state, i.e. CH3CHOad, over both NT and Au/NTsamples, which in turn transformed quickly to yield certain acetate (CH3COOad-) and formate (HCOOad-) type transient species with the involvement of the surface OH groups. The decomposition and oxidation of these surface species with the help of O-2(-), O-ad and hydroxyl ion radicals (OH-) formed at photo-excited Au/NT interfaces led to the reaction products mentioned above. We conclude that, besides electron-hole charge separation, the adsorptive properties of host matrix and nanosize gold may together play a significant role in deciding the photo-catalytic properties of Au/TiO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Acetaldehyde oxidation; Gold co-catalyst; O-2-adsorption; Photo-catalytic activity; TiO2 nanotubes

Synthesis and characterization of high-surface-area Ag2O-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2009)
Nanosized tin dioxide-based powders containing silver and palladium oxides have been prepared by coprecipitation reaction. XRD, TEM, and XPS analysis were carried out for investigation of crystalline structure and surface morphology. The best reactive conditions were determined, such as the concentration of the reactants, pH value, surfactants, reaction temperature, and time. The material obtained is nanocrystalline, having a particle size in the range of 5.21-7.42 nm. Effect of doped-Ag2O on the crystal size of the nanoparticles and the influence of the presence of a second dopant (Pd) on the Ag2O/SnO2 matrix was discussed.
Keywords: Ag2O:SnO2; Nanomaterials; XPS

Vice to virtue: intracellular biogenic nanoparticles for the generation of carbon supported catalysts - Vijayakumar, P. S.; Selvakumar, S.; Gholap, Ramkrishna S.; Singh, A. P.; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2010)
Intracellular biogenic nanoparticles are considered disadvantageous as the separation of the nanoparticles from the biomass becomes intricate. However realizing the importance of carbon supported catalyst for many important organic reactions we envisaged these nanoparticles as a source for carbon supported catalyst. Herein we demonstrate the heat treatment of intracellular biogenic nanoparticles under inert atmosphere as an efficient method for the preparation of carbon supported metal oxide catalysts. Aspergillus ochraceus, a fungus isolated from foundries, on incubation with K(2)TiF(6) led to the synthesis of intracellular titanium oxide nanoparticles. The nanoparticles embedded biomass upon heat treatment at 600 degrees C in a nitrogen environment gave titanium oxide nanoparticles implanted in a carbonaceous matrix. The material thus formed was characterized using FTIR spectroscopy, Raman spectroscopy, HRTEM and X-ray diffraction. Appreciable benzaldehyde selectivity was observed when styrene oxidation was carried out over such immobilized catalysts. The conversion rate was determined to be 76% and the benzaldehyde selectivity was greater than 80%.
Keywords: Benzaldehyde Selectivity; Biosynthesis; Carbon Supported Titania; Nanoparticles; Styrene Oxidation

Degradation of methylene blue via photocatalysis of transition metal-loaded sulfated TiO2 - Gambhire, A. B.; Lande, Machhindra K.; Arbad, B. R.; Rathod, S. B.; Gholap, Ramkrishna S.; Patil, K. R. (Materials Chemistry and Physics, 2011)
Transition metal-loaded nanocrystalline SO42-/TiO2 powders were prepared by sol-gel method. Anatase is found as the active phase in all the samples. Sulfation process clearly stabilizes TiO2 catalyst phase against sintering, maintaining anatase phase and relatively high surface area values with respect to pure TiO2. Wide structural and surface characterization of samples was carried out in order to establish a correlation between the effect of sulfation and metal incorporation on the TiO2 photocatalytic properties. The maximum photocatalytic decomposition of methylene blue solution was achieved with sulfation of TiO2. In addition, incorporation of metal into the structure of SO42-/TiO2 seems to enhance the photocatalytic activity of the samples, which is ascribed to the enlargement of specific surface area, photogenerated carriers separation, light absorption, as well as the higher surface acidity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: nanomaterial; Photocatalytic activity; sol-gel process

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction